The Effect of Soil Density on Infiltration Rate in The Urban Development Area of Padang - Andayono, Totoh (Universitas Negeri Semarang, 2018)
Majority of Padang City residents inhabitant the region along sea shore for residential, public facility and economic center together with all of supporting facilities. That region is seismic prone area, also potentially affected by tsunami hazard and flood.This circumstances pushed local authority of Padang City to develop urban residential area to the north, east and south side of this city (Koto Tangah, Kuranji, Pauh, Lubuk Kilangan and Bungus Teluk Kabung sub-district), which are used to be water infiltration area. The function`s shifting of this area cause the change of soil density. This condition potentially causethe alteration of rainfall infiltration in to the soil.This research was conducted at 15 locations in Dadok Tunggul Hitam area, Koto Tangah sub-district (9 locations in development area and 6 locations in original area condition). Double Ring Infiltrometer are used in this study to predict infiltration rate and Sandcone for measuring soil density.This study used Horton Model to analyze infiltration rate by quantify infiltration rate data(f), constant infiltration rate (fc) and initial infiltration rate (fo). Moreover, regression analysis were used to quantify infiltration rate in order to determine its effects to soil density parameter.The results show that for high density soil (valuegd = 1,00 gr/cm3 to 1,50 gr/cm3), final soil infiltration rate in average is 0,1 mm/minuteto 0,9 mm/minute. This condition can cause decreasingof rainfall`s runoff infiltration capacity. Meanwhile, for low density of soil (valuegd = 0,30 gr/cm3to 1,00 gr/cm3), the infiltration rate value relatively high with final infiltartion rate reached 0,22 mm/minute. This analysis demonstrated that soil density influence the infiltration rate, where 23,7 % of infiltration capacity in Padang City development area is influenced by soil density parameter (gd), and the rest is influenced by other parameters